I9 Listeriosis in neonates and infants in switzerland and canada. (12th March 2018) - Huang, S; Abu Raya, B; Jost, M; Bortolussi, R; Bettinger, J; Grabowski, J; Lacaze, T; Robinson, J; Posfay Barbe, K; Mäusezahl, M; Kollmann, TR
Abstract : Aims: Neonates and infants with listeriosis are at high risk of serious disease outcomes, yet in many countries, little information is reported in routine surveillance. This study aims to begin closing this gap. Methods: Clinicians participating in the Swiss Paediatric Surveillance Unit (SPSU) or the Canadian Paediatric Surveillance Program (CPSP) recorded cases of listeriosis in neonates and infants up to the age of 6 months with information on demographic indicators, manifestation, treatment, clinical course, outcome, exposure and maternal and perinatal risk factors collected. Results: In Switzerland four cases occurred over the first 8 months of the study (April to November 2017). Half of the infants had early-onset disease (EOD, defined as onset of symptoms<7 days of life (DOL)) and the other half had late-onset disease (LOD, defined as onset of symptoms>7 DOL). EOD is considered to be mother-to-child transmitted, while the pathogenesis of LOD is unclear. All cases manifested with sepsis and meningitis, and one EOD case presented with skin- and mucosal lesions as well. All infants made a full recovery with antibiotic treatment with no long-term sequelae noted. Notably, three of the four cases occurred in one hospital during the same week. However, it could not be established whether infection resulted from an epidemiological link between the cases. The Canadian study collected data over 2 years (May-2015 to April-2017). Eight cases of laboratory-confirmed listeriosis were reported in newborns and infants. Six cases had EOD and 2 had LOD. All the six EOD cases presented as septic on DOL 1 (median: 0.5 hours, range: 0–2 hours). All EOD cases had bacteremia and one also meningitis. All EOD cases needed ICU (or NICU) admission; 2 of the EOD cases died. Of the LOD cases, one case became symptomatic on DOL 9 and the other presented on DOL 20 with seizures. Both LOD cases survived the episode, but in one case, the infant suffered permanent sequelae (hemiplegia). Conclusion: While the incidence of neonatal listeriosis recorded in Switzerland exceeded the incidence as could be expected from routine surveillance data, this increase likely related to the unusual cluster of cases. Contrary, the number of cases reported in Canada was far below the incidence as could be expected from the reported incidence of neonatal listeriosis in the literature (table 1). Under-reporting was unlikely as no additional listeriosis were reported through the national notifiable system. This apparent reduction in incidence of EOD could reflect perinatal antibiotic prophylaxis for Group B streptococcus; conclusions about LOD will require longer study period.